PROSES PERBAIKAN BERKELANJUTAN DALAM MEWUJUDKAN SEKOLAH UNGGUL DI SMK NEGERI 3 PATI (Suatu kajian teoritis) - Nugroho, Riadi (Jurnal Pendidikan Ilmu Sosial, 2013)
The aim of this study s to create outstanding school through the implementation of improvingcontinously at SMK Negeri 3 Pati. Arcaro concept about improving continously Quality InEducation: An Implementation, to be reference in exposing this writing. By studying the strengthand weakness that is owned by SMK Negeri 3 Pati therefore, regarding important for studying how isthe process of improving continously through creating quality culture at seven important factors atschool, those are: (1) condusive climate, (2) involving stakeholders as internal and eksternal customersin quality planning, (3) reaching up the hope of academic achievement, (4) giving reward and schoolinsentive, (5) oppurtunity, responsibility, and students’ participation, (6) school regulation anddicipline, (7)conducting curriculum and teaching learning process. Finally, through implementationof this concept can give fresh wind for education institution like SMKN – 3 Pati, to maintain itsposition as outstanding school and ready to compete in international level for the future.